Plastic multicellular development of Myxococcus xanthus: genotype–environment interactions in a physical gradient. Issue 3 (20th March 2019) - Rivera-Yoshida, Natsuko; Arzola, Alejandro V.; Arias Del Angel, Juan A.; Franci, Alessio; Travisano, Michael; Escalante, Ana E.; Benítez, Mariana
Abstract : In order to investigate the contribution of the physical environment to variation in multicellular development of Myxococcus xanthus, phenotypes developed by different genotypes in a gradient of substrate stiffness conditions were quantitatively characterized. Statistical analysis showed that plastic phenotypes result from the genotype, the substrate conditions and the interaction between them. Also, phenotypes were expressed in two distinguishable scales, the individual and the population levels, and the interaction with the environment showed scale and trait specificity. Overall, our results highlight the constructive role of the physical context in the development of microbial multicellularity, with both ecological and evolutionary implications.